2008
DOI: 10.2304/eerj.2008.7.4.459
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Field of Teacher Education Research: Methodology and Issues in a Research Capacity Building Initiative in Teacher Education in the United Kingdom

Abstract: This article discusses the first stages of the work of the Teacher Education Group (TEG) in building research capacity in teacher education research and identifies the potential of the model adopted for future European initiatives in the field. The TEG work is part of the second phase of the Teaching and Learning Research Programme (TLRP), based on an embedded social practices model of research capacity building. The article opens by outlining the broad context of research capacity building initiatives and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Drawing on existing identities and intrinsic interests of staff to build a knowledge base for teacher education (Darling-Hammond 2006;Erixon Arreman and Erixon 2008;Grossman and McDonald 2008;Murray et al 2008) by 'turning the day job into research' was also indicated by our data. These research leaders recommended building teacher educator researcher identities through teacher education inquiry, including self-study (Loughran et al 2004).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Drawing on existing identities and intrinsic interests of staff to build a knowledge base for teacher education (Darling-Hammond 2006;Erixon Arreman and Erixon 2008;Grossman and McDonald 2008;Murray et al 2008) by 'turning the day job into research' was also indicated by our data. These research leaders recommended building teacher educator researcher identities through teacher education inquiry, including self-study (Loughran et al 2004).…”
Section: Discussionmentioning
confidence: 62%
“…There is a concerted effort underway to build a research base for teacher education (Cochran-Smith 2004;Erixon Arreman and Erixon 2008;Grossman and McDonald 2008;Murray et al 2008). Because the responsibility for educating qualified, competent teachers rests primarily within universities, Cochran-Smith (2003) argues that those who teach teachers are the 'linchpins in educational reforms of all kinds' (5).…”
Section: Building Research Capability In Teacher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] As such, the focus of Network 17 can be viewed as an area of specialised and somewhat disconnected activity from the main concerns of EERA with education policy and practice (see Goodman & Grosvenor, 2011). Research on teacher education (Network 10), on the other hand, is commonly understood to represent a contested and often under-researched field (Murray et al, 2008). It produces mainly small-scale research related to practice (and sometimes policy) and is generally nationally focused rather than trans-national and responds to politically driven purposes and practices in teaching and learning (Furlong & Lawn, 2011).…”
Section: Introductionmentioning
confidence: 99%